ANALYSIS OF THE INFLUENCE OF PRODUCT ATTRIBUTES, LOCATION AND PROMOTION ON CONSUMER DECISIONS AT PT. CADIKA BUILDS HARMONIOUS HOUSING CENDANA RESIDENCE SERANG: ANALISIS PENGARUH ATRIBUT PRODUK, LOKASI DAN PROMOSI TERHADAP KEPUTUSAN KONSUMEN PADA PT. CADIKA BANGUN SERASI PERUMAHAN CENDANA RESIDENCE SERANG - Abdul Aziz (Yayasan Education and Social Center, 2022)
This study aims to determine the effect of independent variables (product attributes, location and promotion) on the dependent variable (consumer decisions) at PT. Cadika Builds Harmonious Cendana Residence Housing in Serang City. The research method used is a survey with a quantitative approach. Collecting data obtained by observation, interviews, documentation, questionnaires and literature study. Data were analyzed by calculating multiple linear regression, coefficient of determination analysis and f-test (simultaneous/annova). The results showed that product, location and promotion attributes had a positive effect of 47.61% on consumer decisions, while the remaining 52.39% was influenced by other variables not discussed in this study, such as price, service quality and other independent variables. significant effect on the dependent variable because Fcount > Ftable (59.446 > 2, 72), then H0 is rejected, meaning that there is a significant influence between product, location and promotion attributes on consumer decisions